Exploring the Lived Experiences of Senior High School English Teachers: Challenges, Impact and Coping Strategies in K To 12 Curriculum Implementation - Abdullah, Mahdi B; Bantilan, Bai Laga S; Bolotaolo, Alven M; Reyes, Hilda T Delos; Haron, Guiarmiya M; Uy, Michelle M (RIRAI Publisher, 2025)
This study examines the problems, effects, and coping mechanisms of Senior High School English Teachers in the implementation of the K to 12 Curriculums. Specifically, it sought to answer the following questions: 1. What are the challenges of Senior High School Teachers in terms of: 1.1 teaching methodologies, and 1.2 student assessment? 2. How do these challenges affect the teaching and learning process, particularly students in terms of:2.1. Student’s engagement; and 2.2 Student's English proficiency? 3. What coping strategies or interventions have teachers employed to address these challenges? The experiences of five English instructors from Cotabato City National High School-Rojas were analyzed using a qualitative phenomenological study approach. The findings showed that varying learning styles, resource constraints, and linguistic barriers had an impact on issues in pedagogical approaches, evaluation, and student participation. These obstacles were associated with reluctance, nervousness, and constraints in students' English competence, impeding classroom performance. Strategies such as project-based learning, blended learning, and motivational tactics were utilized to overcome these challenges. Recommendations encompass the implementation of differentiated education, the provision of sufficient resources for new pedagogical methods, and the enhancement of flexible learning methodologies to foster student participation. The study underscores the necessity of tailoring teaching methods to accommodate varied student requirements and utilizing new strategies to address issues in K to 12 Curriculum implementations.